(untitled) (Annals of Medical Research, 2023)
Aim: It is suggested that different formulations of botulinum toxin-A (BoNT-A) used for the same indication might be a factor affecting patient satisfaction. This study aimed to assess patient satisfaction levels in treating upper facial wrinkles (UFW) using various BoNT-A formulations and their association with age and gender. Materials and Methods: This retrospective study included 600 UFW patients treated with different formulations of BoNT-A. The BoNT-A formulations included three different groups: onaBoNT-A (ONA, n:200), aboBoNT-A (ABO, n:200), and praBoNT-A (PRA, n:200). In the patient files or records, satisfaction levels from the BoNT-A application were scored as follows: 1: not satisfied, 2: slightly satisfied, 3: satisfied, 4: very satisfied, 5: completely satisfied. Results: The mean patient satisfaction scores for the ONA and ABO groups were similar, and were higher compared to the PRA group (4.4±0.5 vs. 4.3±0.6 vs. 4.0±0.9, P <0.001, respectively). The mean satisfaction score of the patients aged 18-30 and those aged >60 were lower than the other age group. Among all patients in the 41-50 age range, the patient satisfaction score was higher in the ONA group than the ABO and PRA group. In all female patients, the mean satisfaction score was lower in the PRA group compared to the ONA and ABO groups (P <0.001). Conclusions: While various BoNT-A formulations are generally associated with high patient satisfaction in the treatment of UFW, this can vary depending on age ranges and gender. Evaluating patient-related factors such as age and gender can contribute to the treatment planning for UFW and enhancing treatment adherence.